2022
DOI: 10.1186/s12889-022-12513-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical inactivity in early pregnancy and the determinants in an urban city setting of Kuala Lumpur, Malaysia

Abstract: Background Physical inactivity in pregnancy has been associated with excessive gestational weight gain, hypertensive disorders, gestational diabetes mellitus and postpartum depression. Despite these risks, physical inactivity level remains high especially in higher income countries. The prevalence of physical inactivity among women in Malaysia aged ≥16 years was 28.2% in 2019 exceeding men by 6.1%. However, little is known regarding the subpopulation of pregnant women especially in Kuala Lumpur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The questionnaire was adapted from the studies of Syed Nor et al [ 18 ], Jamil et al [ 19 ], and Humayun et al [ 20 ] (see Multimedia Appendix 1 ). Permission was obtained from all authors to adopt their questionnaires and translate them into the Malay language.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was adapted from the studies of Syed Nor et al [ 18 ], Jamil et al [ 19 ], and Humayun et al [ 20 ] (see Multimedia Appendix 1 ). Permission was obtained from all authors to adopt their questionnaires and translate them into the Malay language.…”
Section: Methodsmentioning
confidence: 99%
“…Personal factors included socio-demographic and biological, behavioral, and psychological factors. Age was not considered to be associated with PA in pregnant women ( 28 , 32 , 37 , 40 , 41 , 43 , 54 , 55 ) by most researchers. Being older appears to be associated with higher MVPA compliance ( 24 , 38 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In one paper, there was a suggestion that PA intensity could be increased by encouraging more PA before pregnancy ( 40 ). Low education ( 32 , 35 , 36 , 43 , 46 , 54 ), first parity ( 29 , 36 , 43 ), lack of knowledge and skills ( 27 , 33 , 44–46 , 53 , 55 ), pregnancy symptoms ( 25 , 27 , 28 , 32 , 33 , 35 , 43 , 44 , 51–53 , 55 ), lack of time ( 25 , 27 , 33 , 39 , 44 , 53 ), low income ( 27 , 33 , 39 , 45 , 51 , 53 ), lack of motivation/goal ( 25 , 51 , 53 , 55 ), and safety concerns ( 25 , 27 , 29 , 31 , 33 , 34 , 44–46 , 49 , 51 , 53 , 55 ) were all identified by the researchers as barriers. The lack of time mainly came from family commitments ( 44 ), while low education, first parity, and lack of knowledge and skills were all related to safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…First, we used backward elimination to remove variables with a p-value >0.2. Second, considering maternal age, level of education, pre-pregnancy BMI, parity, and history of spontaneous abortions to be clinically relevant or related to the level of PA in previous studies [19,20,23], we also added these ve variables into the model. Finally, maternal age, level of education, current employment status, personal monthly income, pre-pregnancy BMI, regular exercise before pregnancy, alcohol consumption before pregnancy, history of spontaneous abortions, parity, stage of pregnancy, nausea and vomiting during pregnancy, and prenatal sleep quality were entered as independent variables into the logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have showed that pregnant women who are younger, less well educated, and unemployed and those with multiple children and a lower income are less likely to engage in an adequate amount of PA [11,12,17,18]. Obstetric variables associated with PA in pregnancy include history of miscarriage, parity, and exercise and smoking status before pregnancy [19][20][21]. Even though there is no scienti c evidence linking prenatal exercise with adverse outcomes, some obstetric caregivers and pregnant women continue to be skeptical about the safety of prenatal exercise.…”
Section: Introductionmentioning
confidence: 99%